2019
DOI: 10.20452/pamw.14905
|View full text |Cite
|
Sign up to set email alerts
|

A panel of urinary biochemical markers for the non-invasive detection of kidney dysfunction in HIV-patients

Abstract: INTRODUCTION The use of antiretroviral therapy in HIV-infected patients can lead to disturbances in kidney function. Renal dysfunction can also be caused by the direct effects of HIV on the kidneys. The assessment of renal function is needed to monitor these patients for the development of chronic kidney disease. OBJECTIVES The aim of this study was to identify urinary biochemical parameters for the assessment of kidney dysfunction in HIV-infected patients. PATIENTS AND METHODS The study included 86 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…According to Brüning et al, 1999, they reported an average of urinary π-GST in German healthy adult being 2.3 ± 0.65 ng/mg creatinine, whereas this marker level in subjects who were exposed with substance-induced kidney disease was 6.0 ± 3.3 ng/mg creatinine [ 51 ]. In addition, the median of urinary π-GST in Polish healthy volunteer with no kidney dysfunction was 3.24 (interquartile range = 2.18–4.12) ng/mg creatinine [ 52 ]. The average urinary π-GST level among healthy subjects, normoalbuminuria, microalbuminuria, and macroalbuminuria was 0.63 (range 0–2.7), 1.35 (range 0–30.6), 1.8 (range 0–33.3), 1.17 (range 0–44.1) ng/mg creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…According to Brüning et al, 1999, they reported an average of urinary π-GST in German healthy adult being 2.3 ± 0.65 ng/mg creatinine, whereas this marker level in subjects who were exposed with substance-induced kidney disease was 6.0 ± 3.3 ng/mg creatinine [ 51 ]. In addition, the median of urinary π-GST in Polish healthy volunteer with no kidney dysfunction was 3.24 (interquartile range = 2.18–4.12) ng/mg creatinine [ 52 ]. The average urinary π-GST level among healthy subjects, normoalbuminuria, microalbuminuria, and macroalbuminuria was 0.63 (range 0–2.7), 1.35 (range 0–30.6), 1.8 (range 0–33.3), 1.17 (range 0–44.1) ng/mg creatinine.…”
Section: Discussionmentioning
confidence: 99%